Interplay of Extracellular Vesicles and TLR4 Signaling in Hepatocellular Carcinoma Pathophysiology and Therapeutics - Stavros P. Papadakos; Konstantinos Arvanitakis; Ioanna E. Stergiou; Christos Vallilas; Stavros Sougioultzis; Georgios Germanidis; Stamatios Theocharis (MDPI AG, 2023)
Hepatocellular carcinoma (HCC) stands as a significant contributor to global cancer-related mortality. Chronic inflammation, often arising from diverse sources such as viral hepatitis, alcohol misuse, nonalcoholic fatty liver disease (NAFLD), and nonalcoholic steatohepatitis (NASH), profoundly influences HCC development. Within this context, the interplay of extracellular vesicles (EVs) gains prominence. EVs, encompassing exosomes and microvesicles, mediate cell-to-cell communication and cargo transfer, impacting various biological processes, including inflammation and cancer progression. Toll-like receptor 4 (TLR4), a key sentinel of the innate immune system, recognizes both pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), thereby triggering diverse signaling cascades and pro-inflammatory cytokine release. The intricate involvement of the TLR4 signaling pathway in chronic liver disease and HCC pathogenesis is discussed in this study. Moreover, we delve into the therapeutic potential of modulating the TLR4 pathway using EVs as novel therapeutic agents for HCC. This review underscores the multifaceted role of EVs in the context of HCC and proposes innovative avenues for targeted interventions against this formidable disease.